Aimai Hyougen Sebagai Cerminan Komunikasi Implisit Jepang - Maharani Patria Ratna (IZUMI, 2019)
(Title: Aimai Hyougen as a reflection of Japanese implicit Communication) Japanese is known for its politeness in communication. There are many ways to express politeness in Japanese, having an implicit communication is one of them. This may cause some troubles to foreigners to understand Japanese communication. So, it is important to know the style of Japanese communication to avoid misunderstandings. The purpose of this study is to describe japanese implicit communication style. This study is done by searching some references from trusted sources so that the style of Japanese implicit communication can be concluded. The results of this study are there are some keywords in Japanese that usually contain implicit meaning such as chotto, saa, demo, muzukashi, ii desu. Those word represent Japanese communication style. Japanese who use those words are highly predicted that there are something that is hard to tell to the interlocutor. Beside those word, understanding Japanese culture especially communication culture is also important. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor